A reorganização das relações de produção no campo: agronegócio e trabalho (Oeste do Paraná, final do século XX e início do século XXI) (Revista de História Regional, 2020)
The article introduces the results of research on the history and historiography of the social experience of diverse subjects related to the poultry industry in western Paraná, Brazil, from the 1970s and early twenty-first century. With the diversification and technification of agricultural activities on small properties, molded by agribusiness from the 1990s, the work has not only familiar, occurring to the hiring of workers to work in the agricultural production, which changed working relationships in the field.